(untitled) (Research, Society and Development, 2022)
Objective: to synthesize the scientific production on educational methodologies applied in the teaching of nursing theories at undergraduate, graduate and professional levels. Method: integrative review of the literature performed in the databases: Medical Literature and Retrivial System onLine (MEDLINE/PubMed®); SCOPUS (Elsevier); Latin American and Caribbean Health Sciences Literature (LILACS) and Nursing Database (BDENF). The PICo methodology was used to construct the research question and select descriptors, as: "nursing theories", "teaching", "educational technology" and "nursing education". Seven articles published from 1994 to 2022 were selected. Results: The educational methodologies mentioned by the authors of the studies analyzed in the teaching of nursing theories are: traditional method, gamification, audiovisual resources, simulation and self-directed learning. Conclusion: the use of diversified educational methodologies is effective in teaching nursing theories by promoting playful and interactive approaches, as it provides students, graduate students, and professionals with the development of necessary skills for the exercise of professional practice.